Pengaruh Motivasi terhadap Kinerja Guru Madrasah Aliyah Negeri Pangkep - Kurniati Kurniati (Madrasah Tsanawiyah DDI Cilellang, 2022)
This study aims to analyze the effect of motivation on the performance of Madrasah Aliyah Negeri Pangkep teachers. This research is a survey research with a quantitative approach. The population of the number of teachers in MAN Pangkep is 32 teachers, because the population is less than 100 so the entire population is determined as respondents. Data were collected using observation, questionnaire, and documentation techniques. The research instruments used were observation sheets, questionnaires, and checklists (guidelines) for documentation. The research data was processed using the SPSS Version 23 application. The output of data processing was then analyzed by simple linear regression analysis (t-test) after going through the validity and reliability tests. The results of simple linear regression analysis (t-test) show that the value of Sig. of 0.004, means the value of Sig. <0.05 (0.004 <0.05). These data indicate that motivation has an effect on teacher performance at Madrasah Aliyah Negeri Pangkep. The value of R Square is 0.494 so that the motivation variable has an influence of 49.4% on the teacher performance variable. While the other 50.6% are influenced by other variables not examined in this study.